An Object-Oriented World-View for Intelligent, Discrete, Next-Event Simulation - Burns, James R.; Morgeson, J. Darrell (Management Science, 1988)
Concepts from software engineering and knowledge engineering are incorporated into discrete, next-event simulation. The existing, conventional world-view utilized within discrete simulation is reviewed. A construct is presented that makes existing discrete simulation world-views more robust for problems involving endogenous decision-making. The use of knowledge bases and inference engines as mechanisms for modeling such decision making is presented. The result is a simulation world view that is able to simulate systems involving intelligent decision-making entities (actors) whose decisions strongly impact the state of the system.